Vejrforholdene i Landbrugsaaret 1944—45. (Fra 1. Oktober 1944 til 30. September 1945). - Hansen, H. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1944—45. (Fra 1. Oktober 1944 til 30. September 1945).